Pengembangan Aplikasi Android Pembelajaran Gamelan Selonding Gaya Tenganan - Komang Ayu Tri Paramitha; I Wayan Diana Putra; Ni Wayan Mudiasih (Journal of Music Science, Technology, and Industry, 2022)
Purpose: The purpose of this research is to develop an android application for learning Selonding Instrument of Tenganan Style. Research Method: The type of this research is used Research and Development (R&D). The result of this research is an android-based Selonding Instrument learning application, namely learning activities or subject matter which is divided into several substances such as basic knowledge of Gamelan Selonding, instrumentation, tone structure, saih (tone tasks), the basic technique of using the application, game techniques, song and quiz questions related to Selonding Instrument. Result and discussion: The results of the validation of the learning content expert test with a percentage of 93.34%, the results of the validation of the learning media expert test with a percentage of 96.67%, the validation results of the learning design expert test with a percentage of 90%, the results of the musical teacher trial with a percentage of 96.67%, the results of individual trials with a percentage of 92% and the results of small group trials with a percentage of 94.5% stated that the results of the application were very good. Implication: The development used in developing learning applications is in the form of a Borg and Gall product development model